Pengembangan Bahan Ajar Buku Teks IPS Tema Indahnya Kebersamaan Pada Peserta Didik Kelas 4 MI An Nuriyah Kwanyar Bangkalan - Nurul Makrifah Faqih; Nur Fauzi (Fikroh: Jurnal Pemikiran dan Pendidikan Islam, 2020)
This research aims to develop Social Science Textbook teaching materials. The material teaching is developed in the form of social studies textbooks with the theme "Beautiful Togetherness" and appropriate based on student’s expertise and readability as seen from the material or content, linguistic, presentation, and graphic aspects. This research is a research and development study with the design of analysis, planning, and developing textbook development. The feasibility of the expert test was carried out by material experts and media experts, while the students' openness test was carried out by the 4th grade students of MI An-Nuriyah from group A with a total of 36 students and 4th grade students of MI An-Nuriyah from group B with a total of 32 students. The ttechnique of Collecting data is done using a questionnaire. The method used to analyze data is quantitative descriptive analysis techniques by the distribution of five scales and the rating scale predetermined. Textbooks are well considered by material experts and media experts that has a minimum average score "enough" category. The text book feasibility test results the assesment Experts in the "good" category. Evaluation of textbooks by media experts are "enough" and "good" categories. The results of the textbook feasibility test by textbook students are categorized as "good."